Development Of Fermented Water Kefir Amaranth Drink - Chin, Wen Yi (Universiti Sains Malaysia, 2020)
The aim of this study is to develop fermented water kefir drink from vegetable amaranth juice as an alternative for vegetarians and lactose intolerants to replace dairy beverages. Various analyses were conducted on fermented water kefir red amaranth (Amaranthus tricolor) and green amaranth (Amaranthus blitum) drinks fermented with selected sugar levels (5% and 7%). Both fermented red and green amaranth samples with 7% sugar achieved significant (p<0.05) decrement in pH value, total soluble solids, and sucrose concentration which represented efficient water kefir fermentation. Fermented red amaranth sample showed significant (p>0.05) increment in antioxidants activity and total phenolic content after fermentation represented higher nutritional value. Both fermented red and green amaranth samples were able to claim probiotic properties due to the achievement of minimum 106 CFU/mL of lactobacillus after 2 weeks of storage. Results from microbiological analyses showed a significantly (p<0.05) higher lactobacilli count (13.39 x 106 CFU/mL) and yeast and mold count (25.23 x 106 CFU/mL) in fermented red amaranth drink with 7% sugar level compared to green amaranth. Both samples had acceptable range of coliform count and absence of fecal coliforms represented the stable microbial quality. However, red and green amaranth vegetable juice were not fully suitable to use as water kefir substrate due to low titratable acidity and total viable cell count. As an overall, fermented red and green amaranth water kefir drinks were successfully produced.